Simulation Protocol for Prediction of a Solid-Electrolyte Interphase on the Silicon-based Anodes of a Lithium-Ion Battery: ReaxFF Reactive Force Field - Yun, Kang-Seop; Pai, Sung Jin; Yeo, Byung Chul; Lee, Kwang-Ryeol; Kim, Sun-Jae; Han, Sang Soo (American Chemical Society, 2017)
We propose the ReaxFF reactive force field as a simulation protocol for predicting the evolution of solid-electrolyte interphase (SEI) components such as gases (C2H4, CO, CO2, CH4, and C2H6), and inorganic (Li2CO3, Li2O, and LiF) and organic (ROLi and ROCO2Li: R = -CH3 or -C2H5) products that are generated by the chemical reactions between the anodes and liquid electrolytes. Re-IYFF was developed from ab initio results, and a molecular dynamics simulation with ReaxFF realized the prediction of SEI formation under real experimental conditions and with a reasonable computational cost. We report the effects on SEI formation of different kinds of Si anodes (pristine Si and SiOx), of the different types and compositions of various carbonate electrolytes, and of the additives. From the results, we expect that ReaxFF will be very useful for the development of novel electrolytes or additives and for further advances in Li-ion battery technology.